Intra-articular delivery of AAV vectors encoding PD-L1 attenuates joint inflammation and tissue damage in a mouse model of rheumatoid arthritis - Li, Wenjun; Sun, Junjiang; Feng, Susi Liu; Wang, Feng; Miao, Michael Z.; Wu, Eveline Y.; Wallet, Shannon; Loeser, Richard; Li, Chengwen (Frontiers in Immunology, 2023)
Rheumatoid arthritis (RA) is the most common form of autoimmune inflammatory arthritis. Intra-articular gene delivery to block proinflammatory cytokines has been studied in pre-clinical models and human clinical trials. It has been demonstrated that decreased expression of programmed death-ligand 1 (PD-L1) is associated with rheumatoid arthritis (RA). In this study, we explored the therapeutic role of PD-L1 in preventing RA development and progression by intra-articular delivery via adeno-associated virus (AAV) vectors in a collagen-induced arthritis (CIA) mouse model of RA. After administration of AAV5/PD-L1 vectors, strong PD-L1 expression was detected in AAV transduced joints. Joints treated with PD-L1 at the time of arthritis induction exhibited significantly less swelling and improved histopathological scores when compared to untreated joints. Additionally, the infiltration of T cells and macrophages was decreased in joints of CIA mice that received AAV5/PD-L1 vectors (P<0.05). The levels of pro-inflammatory cytokines, including IL-1, IL-6, IL-17 and TNFα, were lower in AAV5/PD-L1 treated than untreated joints (P<0.05). Furthermore, the administration of AAV5/PD-L1 vectors into the joints of CIA mice did not impact serum cytokine levels and the antibody titers to type II collagen. Biodistribution of AAV vectors after intra-articular injection showed undetectable AAV genomes in other tissues except for a low level in the liver. Similar to the results of AAV5/PD-L1 vector administration on day 0, decreased joint swelling and lower histopathological damage were observed in joints treated with AAV5/PD-L1 vectors on day 21. The results from this study demonstrate that local AAV mediated PD-L1 gene delivery into the joints is able to prevent the development and block the progression of arthritis in CIA mice without impacting systemic immune responses. This approach provides a novel strategy to effectively prevent and block progression from early inflammatory joint diseases using local AAV gene therapy by interference with immune checkpoint pathways.